The Role of Non-State Actors for Refugees in Turkey: Local Integration of Syrian Refugees in Mersin - Sever, Barış Can, M.A. (Tectum Verlag, 2020)
In this research, the theoretical and conceptual debates on the local integration of refugees and the role of non-state actors in the integration are brought together. Their investigation take place in the nexus of migration management, the implementation of the states and non-state actors on the field. Particularly, the local integra-tion is examined through the Syrians’ stay in Mersin/Turkey. In the methodology part of this research, semi-structured interviews were applied to 20 non-state actors in Mersin (Summer 2017) in order to have an idea about the role that they have played in the local integration of Syrian refugees. In this way, while the profiles of selected non-state actors in the field were revealed, their participation and contribution to the integration pro-cess were interpreted.